STRATEGI SUMBER DAYA MANUSIA DALAM PENERAPAN SISTEM PENGHARGAAN BERBASIS KINERJA UNTUK MOTIVASI KERJA - Rifai, Mesrawati; Himawan, Ferdiansyah; Rendi, Rendi; Masnama, Masnama; Nengsih, Hijrana (Yayasan Education and Social Center, 2024)
This research examines the implementation of a performance-based reward system through a qualitative approach with a case study design, involving 15 informants from the service industry in Indonesia. Data was obtained through in-depth interviews, participant observation, and document analysis. Findings show 60% of organizations are adopting a hybrid approach that integrates financial and non-financial elements, while 25% are still maintaining traditional systems. System transparency (92%) was identified as a critical success factor, followed by management support (87%) and cultural fit (83%). Top challenges include technology integration (65%) and resistance to change (58%). This research highlights the importance of adapting reward systems in line with employee needs and the organizational cultural context. The practical implications of these findings suggest the need for integration of reward systems with organizational strategic goals and a gradual approach in system transformation to achieve optimal results in increasing employee motivation and job satisfaction.